Strategies of using ICT in education : the case of Malaysia. - Osman, Mohd Nizam; Shahkat Ali, Muhammad Sham (2008)
The inter-relationship between the system of education and the quality of the workforce in Malaysia has been the subject of numerous discussions and debates in both academic and business circles. These debated obviously indicate the positive link between the system of education and the need to inculcate the use of technology in the system of education. As one of the means of moving towards an economy that is based on knowledge-driven, the government feels it is necessary to expand the extent of ICT-related usage, including computing system and other forms of ICT across the various sectors in the country, including education. One of the means of achieving these objectives is to introduce the use of ICT in education across all schools throughout the country. In relation to this move, a number of initiatives have been introduced and developed, such as the smart school concept, e-learning concept within the higher education context and the use of sophisticated technology driven within the schools. The education curriculum has also been changed to accommodate the use of these technologies within the educational curriculum. Although these moves are seen as central towards enhancing the use of ICT-related technologies in education, however there are a number of questions that will have to be raised here. These include, i) are the students and teaching staff ready to use ICT-related technologies extensively as one of the teaching tools in schools?, ii) are the facilities in schools capable to accommodate education through the use of ICT-related technologies?, and more importantly iii) are the government strategies to invest heavily in using ICT in education is seen strategic in achieving the aspirations of transforming the Malaysian economy from an agricultural-based to knowledge-driven economy? These questions are central to the study and will be addressed in greater depth in the study. As a means of exploring this issue in greater depth, the study incorporates both qualitative and quantitative data to examine respondents' views and perceptions about the use of ICT in education. Apart from this, the study also incorporates secondary data to support the study. These data are largely obtained from printed materials from books, articles, newspapers reports and government reports. As a means of collecting quantitative data for the study, a total 200 survey forms have been distributed to a carefully selected students and teaching staff in private and government schools and institutions of higher education in the State of Selangor, Malaysia. The data obtained from the completed questionnaire surveys will be analyzed using SPSS software to examine respondents' views and perceptions regarding the issue being studied.